The Impact of COVID-19 on Plastic Surgery Residency Training - Zingaretti, Nicola; Contessi Negrini, Filippo; Tel, Alessandro; Tresoldi, Marco Mario; Bresadola, Vittorio; Parodi, Pier Camillo (Aesthetic plastic surgery, 2020)
Nowadays didactic and surgical activities for residents in the surgery field are less and less due to an increasing burden of documentation and “non-educational work.” Considering the current lockdown due to the COVID-19 pandemic, it has never been so important to find different ways to allow residents to improve their knowledge. We asked all plastic and esthetic surgery residents in our country to fill out a questionnaire to investigate changes in their didactical activity and analyze problems about their professional growth in the last few months. From the results of such questionnaires, we found that most of the residents feel the decrease in surgical activities during this time is a detrimental factor for their training and that even if all the schools have changed their didactical activities no school has introduced the use of virtual simulators to compensate for the decrease in surgical practice. Actually, the majority of residents use webinars to keep updated, stating that such technologies are useful but not sufficient to analyze plastic surgery topics in depth during COVID-19 lockdown. Virtual interactive tools are well known in different clinical and surgical specialties, and they are considered as a valid support, but it seems that in plastic surgery they are not so used. According to the most recent studies about residents’ didactical program, we have investigated the potential of Anatomage Table in combination with Touch Surgery application as physical and mental aids to bypass the decreased number and kind of surgical interventions performed in this particular time. Anatomage is an academic user-friendly touch screen table; it is used by both medical students and residents to learn human anatomy and to master surgical anatomy. Touch Surgery is an application available on smartphones and tablets that gives the possibility to watch real and virtually designed surgical videos, accompanied by explanatory comments on the surgical phases; they are interactive and give the possibility to check what you have learned through tests administered after virtual classes. In our opinion, these tools represent reliable solutions to improve plastic residents’ training, mostly during the COVID-19 pandemic. Level of Evidence V This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .